The great unravel - Davis, Kent, 1970- (Davis, Kent, 1970- Riddle in Ruby, 2017)
When an evil scientist Dr. Swedenborg invents a machine that steals people's life forces, Ruby and her friends may be the only ones brave enough to stop him.